Key Success in The Transformation from Volume-Based to Value-Based Healthcare: A Scoping Review - Edy Gunawan; Mardiati Nadjib; Syarifah Soraya (Syntax Corporation Indonesia, 2022)
The medical cost trend had been increasing faster than the global inflation rate. Higher costs posed a significant problem for healthcare providers, payers, and eventually patients. The concept of value-based healthcare (VBHC), which emphasized the importance of measuring outcomes relative to the costs, was introduced to mitigate the impact of these medical trends. This research used a scoping review methodology to describe the factors that affect the shift from the conventional volume-based healthcare to value-based healthcare. Data of research based on article search was conducted using online Scopus and Embase databases, resulting in 800 articles describing value-based healthcare. Duplication removal excluded 76 articles, screening excluded 295 articles, eligibility assessment excluded 76 articles, and the remaining 30 articles were included. The results of study show that VBHC was proposed as a shift in healthcare management entailing six reinforcing elements, but most hospitals have implemented only one VBHC element. The most common implemented elements are “the measurement of outcome and cost” and “the reorganization to integrated practice units.” The key success for the implementation of these elements are: (1) strong data collection to measure clinical outcomes that matter to patients, (2) clear governance of this data management, and (3) strong support from the high leadership to encourage multidisciplinary teamwork. Thus, the true VBHC system can only be reached when all the six elements are achieved. However, no single study describes a success in implementing all elements of VBHC. Hospital leaders need to be cautious when interpreting VBHC as not to think that the VBHC can be reached by cherry-picking only selected elements of VBHC.